Challenges and benefits of post-lithium-ion batteries. (16th January 2020) - Walter, Marc; Kovalenko, Maksym V.; Kravchyk, Kostiantyn V.
Abstract : Post-Li-ion batteries based on Na, Mg, and Al offer substantial electrochemical and economic advantages in comparison with Li-ion batteries. Abstract : At present, rechargeable batteries composed of sodium, magnesium and aluminum are gaining attention as potentially less toxic and more economical alternatives to lithium-ion batteries. From this perspective, the last two decades have seen a surge of reports on various anodes and cathodes for post-lithium-ion batteries, including sodium-, magnesium-, and aluminum-ion batteries. Moreover, the new electrochemical concept of dual-ion batteries, such as magnesium–sodium and aluminum–graphite dual-ion batteries, has recently attracted considerable attention. In this focus article, the operational mechanisms of post-lithium-ion batteries are discussed and compared with lithium-ion technology, along with core challenges currently limiting their development and benefits of their practical deployment.